2019
DOI: 10.1111/eci.13061
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of serum nitrite and nitrate, NOx, are associated with increased total and cardiovascular mortality in an 8‐year follow‐up study

Abstract: Background Nitric oxide (NO) is one of the key regulators of vascular function. Abnormal NO signalling is linked to various cardiovascular diseases. We studied associations between circulating levels of NO metabolites, nitrite and nitrate (NOx) and total and cardiovascular mortality in a prospective 8‐year follow‐up cohort study in 1869 patients aged over 55 years. Materials and methods The Cox proportional hazard ratio (HR) regression models were adjusted for multiple risk‐related variables. Post hoc Kaplan‐M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(66 reference statements)
1
10
0
1
Order By: Relevance
“…These results are in general agreement with our previous observations indicating that high levels of NOx are independent short-term risk factors of cardiovascular mortality (20). These studies have been confirmed in our previous study and another long-term study of cardiovascular and total mortality and morbidity (19,34). In general, changes in the expression of adiponectin can reduce oxidative stress and enhance the endothelial production of NO in an animal model (6), whereas oxidative stress may influence the expression of adiponectin in perivascular adipose tissue (35) thus forming a complex of regulatory feedback pathways.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results are in general agreement with our previous observations indicating that high levels of NOx are independent short-term risk factors of cardiovascular mortality (20). These studies have been confirmed in our previous study and another long-term study of cardiovascular and total mortality and morbidity (19,34). In general, changes in the expression of adiponectin can reduce oxidative stress and enhance the endothelial production of NO in an animal model (6), whereas oxidative stress may influence the expression of adiponectin in perivascular adipose tissue (35) thus forming a complex of regulatory feedback pathways.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it was hypothesized that genetic polymorphisms of the ADIPOQ or EDN1 genes may influence the circulating levels of vasoactive mediators and may be associated with the clinical manifestations of atherosclerosis. Stable metabolites of NO, (nitrite and nitrate NOx), are of particular relevance as recent studies indicate that circulating NOx levels are linked to cardiovascular mortality (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…NO x is a biomarker of NO in clinical studies, as it represents the sum of the breakdown products of NO, nitrate (NO 3 − ) and nitrite (NO 2 − ). 44 To measure serum calcification propensity (OD 650 ), equimolar (2 mmol/L) concentrations of CaCl 2 and Na 2 HPO 4 were added to the serum of the subjects in 96-well plates (100 µL serum per well). Upon 24 hours incubation at 37 °C in the presence of 5% CO 2 (v/v), the change in the optical density at a 650 nm wavelength (OD 650 ) was monitored by comparing the serum with or without calcium/phosphate supplementation.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The levels of NOx have been recently extensively characterized by us and other authors as independent predictors of cardiovascular mortality and acute cardiovascular events, including follow up studies for 3 27 and 8 years 28 in a Moscow cohort, a relatively small study in elderly patients in Japan 29 , a Framingham offspring study 30 , and a similar study in Iran 31 . The results of the present study indicated independent associations of high levels of NOx with risk for AMI in all tested models (Tables 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%